PSYCHOLINGUISTIC BASES OF WORK WITH THE TEXT AT THE LESSONS OF RUSSIAN LANGUAGE AND LITERATURE - Gulnoza Narimonova (Western European Studies, 2024)
Modern text-oriented Russian language teaching is based on the achievements of Russian philology and psycholinguistics. Psycholinguistics - the theory of speech activity - gives an idea of the correlation between language and consciousness, speech and thinking. The interests of this science lie in determining the psychological features of the relationship between linguistic consciousness and human social activity, social being and life of linguistic individuals
Keywords: Modern Teaching; Psycholinguistics; Speech Activity; Linguistic Consciousness